Introduction to Optimization - Krishnasamy, Ganesh; Kulkarni, Anand Jayant; Abraham, Ajith (Cohort Intelligence: A Socio-inspired Optimization Method, 2017)
For almost all the human activities there is a desire to deliver the most with the least. For example in the business point of view maximum profit is desired from least investment; maximum number of crop yield is desired with minimum investment on fertilizers; maximizing the strength, longevity, efficiency, utilization with minimum initial investment and operational cost of various household as well as industrial equipments and machineries. To set a record in a race, for example, the aim is to do the fastest (shortest time).